Guidelines for the rational design and engineering of 3D manufactured solid oxide fuel cell composite electrodes - Bertei,A; Tariq,F; Yufit,V; Ruiz,Trejo E; Brandon,N (Journal of the Electrochemical Society, 2016)
The growth of 3D printing has opened the scope for designing microstructures for solid oxide fuel cells(SOFCs) with improved power density and lifetime. This technique can introduce structural modifications at a scale larger than particle size but smaller than cell size, such as by insertingelectrolyte pillars of ~5-100 µm. This study sets the minimum requirements for the rational design of 3D printedelectrodes based on an electrochemical model and analytical solutions for functional layers with negligible electronic resistanceand no mixed conduction. Results show that this structural modification enhances the power density when the ratio keffbetween effective conductivity and bulk conductivity of the ionic phase is smaller than 0.5. The maximum performance improvement is predicted as a function of keff. A design study on a wide range of pillar shapes indicates that improvements are achieved by any structural modification which provides ionic conduction up to a characteristic thickness ~10-40 µm without removing active volume at the electrolyte interface. The best performance is reached for thin (< ~2 µm) and long (> ~80 µm) pillars when the compositeelectrode is optimised for maximum three-phase boundarydensity, pointing towards the design of scaffolds with well-defined geometry and fractal structures.